2010
DOI: 10.1016/j.agee.2010.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Changes in soil respiration across a chronosequence of tallgrass prairie reconstructions

Abstract: Close relationships among climatic factors and soil respiration (R s) are commonly reported. However, variation in R s across the landscape is compounded by site-specific differences that impede the development of spatially explicit models. Among factors that influence R s , the effect of ecosystem age is poorly documented. We hypothesized that R s increases with grassland age and tested this hypothesis in a chronosequence of tallgrass prairie reconstructions in central Iowa, U.S.A. We also assessed changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
2
9
0
1
Order By: Relevance
“…However, we observed no significant difference in accumulated CO 2 among 1-4-year-old grasslands. Although the difference in age among grasslands may have been too small to show an effect (Maher et al, 2010), our results indicates that the build-up of C in grassland soil increases with grassland age, which was supported by the results in Franzluebbers and Stuedemann (2003). No significant difference in CO 2 emissions was observed with slurry application, which was consistent with the results for poultry manure applied in grassland (Franzluebbers and Stuedemann, 2003).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, we observed no significant difference in accumulated CO 2 among 1-4-year-old grasslands. Although the difference in age among grasslands may have been too small to show an effect (Maher et al, 2010), our results indicates that the build-up of C in grassland soil increases with grassland age, which was supported by the results in Franzluebbers and Stuedemann (2003). No significant difference in CO 2 emissions was observed with slurry application, which was consistent with the results for poultry manure applied in grassland (Franzluebbers and Stuedemann, 2003).…”
Section: Discussionsupporting
confidence: 82%
“…The root biomass increases with age of grassland. Maher et al (2010) observed significant linear increase in root biomass with the age of grasslands from an experimental site in Iowa, USA. Estimates show that organic C in soil derived from roots of temperate arable land and grassland species during a growing season is in the range of 0.1-2.8 t ha −1 ; perennial ryegrass contributing to 2.8 t ha −1 (Rees et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Reconstructed prairies in southern Minnesota produced approximately 5 Mg ha −1 of aboveground biomass without N fertilization and almost 8 Mg ha −1 with N fertilization (Camill et al, 2004). Reconstructed prairies in central Iowa, ranging in age from 4 to 12 yr, produced between 3.4 and 8.6 Mg ha −1 of aboveground biomass with productivity generally increasing with prairie age (Maher et al, 2010). An annually burned portion of a native prairie in northeastern Kansas produced approximately 9.8 Mg ha −1 of aboveground biomass at lowland sites and approximately 4.5 Mg ha −1 of aboveground biomass at upland sites (Nippert et al, 2011).…”
mentioning
confidence: 99%
“…En este contexto, la producción del ecosistema pastizal se encuentra influenciado por la composición florística y los microbios del suelo, que interactúan con el ambiente que les rodea; factores del suelo, como la temperatura, humedad, y sustrato influyen simultáneamente en el rendimiento vegetal (Raich & Tufekcioglu, 2000). Maher et al (2010) encontraron un aumento significativo de la respiración en pradera vieja y una correlación positiva con la biomasa de raíces y la productividad primaria neta durante el crecimiento del pastizal, e indicaron que la temperatura del suelo es un fuerte predictor de la respiración intra-estacional entre praderas. De manera que la humedad del suelo fue el factor ambiental dominante que controló la variación estacional e interanual de la respiración del prado a temperatura constante de 10°C (Lawrence & Bruce, 2005), lo que implicó mayor producción de biomasa en las parcelas con prácticas de conservación "surcos" y "hoyos".…”
Section: Resultados Y Discusión Estado Ecológico Del Pastizalunclassified